The Black Campus Movement : Black Students and the Racial Reconstitution of Higher Education, 1965-1972. - Rogers, Ibram H. H. (Palgrave Macmillan, 2012)
This book provides the first national study of this intense and challenging struggle which disrupted and refashioned institutions in almost every state. It also illuminates the context for one of the most transformative educational movements in American history through a history of black higher education and black student activism before 1965.